World Cup 2018: Already the Most Expensive Ever? - Müller, Martin; Wolfe, Sven Daniel (My University, 2014)
At USD $21 billion, the World Cup 2018 in Russia is on course to become the most expensive ever. Cost overruns at this early stage suggest, however, that the ﬁnal bill will be much higher: the price tag for the 12 stadia has already grown from an initial USD $2.8 billion to now USD $6.9 billion, although construction on most venues has not even started. The projected costs place the Russian stadia among the most expensive worldwide. At USD $11,600, the costs per seat are more than double those in Brazil. In a stagnating ticket market in Russia’s premier league, the new venues will exacerbate overcapacities. With the economic outlook for Russia darkening, the World Cup 2018 is likely to become a deadweight to Russian economic development through the misallocation of scarce resources.